Surgical and oncological outcome after extended lymph node dissection for carcinoma of the stomach and the esophagogastric junction: a retrospective analysis from an experienced single center - Dimitrios Raptis; Matthias Maak; Christian Krautz; Susanne Merkel; Maximilian Brunner; Abbas Agaimy; Arndt Hartmann; Sabine Semrau; Oliver Ott; Rainer Fietkau; Jürgen Siebler; Robert Grützmann; et al. (Archives of Medical Science, 2021)
Introduction Gastric cancer remains the fourth leading cause of cancer-related death in Europe, while the proportion of adenocarcinomas of the esophagogastric junction has risen by more than one third over recent years. In 2018, 14,700 new cases of gastric cancer were estimated in Germany, while the 5-year relative survival rate is reported to be 33% for women and 30% for men; in the USA almost the same rate was reported, with 31% 5-year survival.